(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents the results of the study of the resistance to drought and heat, which are the valuable traits of Durum wheat varieties and lines studied in the field of advanced yield trial nursery of Durum wheat in dry areas, in laboratory conditions. Based on the results of the analysis, four varieties and lines of Durum wheat high resistance to drought and heat were selected for use in the selection process